Profitability as a Moderator in the Effect of RGEC-Based Banking Health on Firm Value: Evidence from IDX-Listed Banks (2019–2023) - Marsifa; Gursida, Hari; Indrayono, Yohanes (Asosiasi Ahli Administrasi Indonesia, 2025)
This study examines the effect of banking health, measured using the RGEC method comprising Risk Profile (Non-Performing Loans/NPL), Good Corporate Governance (GCG), Earnings (BOPO), and Capital (Capital Adequacy Ratio/CAR), on firm value with profitability, represented by Return on Assets (ROA), as a moderating variable. The research is driven by inconsistencies between theoretical expectations and empirical data in Indonesia’s banking sector during 2019–2023. It aims to determine the extent to which RGEC components affect firm value and whether ROA strengthens or weakens these relationships. The sample consists of banking companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. A quantitative approach is employed using panel data regression to examine direct effects and Moderated Regression Analysis (MRA) to assess interaction effects. The findings reveal that the impact of NPL, GCG, BOPO, and CAR on firm value (measured by Price to Book Value/PBV) varies across indicators. While ROA significantly influences firm value, its moderating effect is only partially confirmed. These results indicate that profitability does not consistently amplify the influence of RGEC variables on firm value, suggesting the presence of other influencing factors such as macroeconomic conditions or managerial practices. This study emphasizes the importance of strengthening financial performance alongside good governance, effective risk management, and capital efficiency to enhance sustainable firm value. The findings provide practical implications for bank managers and regulators in aligning profitability strategies with efforts to increase market valuation.